Infecções Fúngicas Associadas à COVID-19 no Brasil (Revista Brasileira Multidisciplinar, 2026)
At the end of 2019, in the Chinese city of Wuhan, a series of cases caused by a new virus from the Coronaviridae family, SARS-CoV-2, emerged, sparking a pandemic that became one of the most devastating in modern history. This was due not only to the initial infection but also to subsequent complications, such as coinfections with other microorganisms and persistent effects in the intermediate and advanced stages of the disease. This review aims to discuss the fungal coinfections most associated with COVID-19 in Brazil, as well as the pathophysiology and epidemiology of the main species isolated, primarily in hospital environments. To achieve this, a literature review of scientific articles published from 2020 to 2023 was conducted on major research platforms and government websites. The study showed that the invasive fungal infections most associated with COVID-19 are caused by opportunistic fungi that exploit the patient's immunological vulnerability to cause the most severe form of the disease, including invasive aspergillosis, candidemia, mucormycosis, and cryptococcosis. Currently, this topic is of critical importance for healthcare professionals and the population to understand the risks fungi pose to COVID-19 patients, presenting a significant problem in fragile hospital settings and highlighting the need to prevent such infections.
Keywords: covid-19; invasive fungal infections; epidemiology and covid-19; hospital fungal infections; funfus covid-19 coinfection; Brazil